Bio-innovations genome-edited crops for climate-smart food systems - Falck-Zepeda, José B.; Biermayr Jenzano, Patricia; Roca, Maria Mercedes; Fuentes-Campos, Ediner; Kikulwe, Enoch Mutebi (International Food Policy Research Institute, 2022)
As growing populations, changing diets, and climate change affect growing conditions for crops, our agriculture and food systems must increase production and productivity to ensure access to healthy and diverse diets for all. The expanding demands on agriculture and food systems must be met without increasing pressure on the environment, and while accomplishing other development goals and objectives. Addressing this complex problem requires the identification of game-changing interventions that can drive sustainable, equitable agriculture for food system transformation. “Bio-innovations” will be one key set of interventions. Bio-innovations encompass biotechnology-based tools and product innovations, as well as innovations in their governance, regulation, and social and business contexts. They hold potential to contribute to food system transformation by accelerating productivity growth and reducing agriculture’s environmental footprint, as well as contributing to climate change adaptation and mitigation.